The impact of intrinsic motivation on employees’ job performance / Nurdiyana Nazihah Zainal ... [et al.] - Zainal, Nurdiyana Nazihah; Jamaludin, Mohd Fazil; Rahim, Azira; Hassam, Siti Fairuza; Ardeela, Bebe Nur; Khan, Mohamad Yunus (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Job performance is one of the important criteria in the success of every business. Therefore, it is a priority task for the management of the business to motivate their employees so that they are able to produce consistency in their job performance. The purpose of the study is to investigate the impact of intrinsic motivation to increase their job performance at work. The determinants are focusing on the intrinsic motivation which are job autonomy, mastery and self-efficacy. This study will focus on the employees who are in automotive industry which is still under research especially using intrinsic motivation as the determinants. Questionnaires were distributed to 152 employees who are currently working in the automotive industry. Respondents were selected using convenience sampling due to indefinite and unreached number of population data. However, respondents who are presently working in the automotive industry were the main criteria of the selected respondents. Data collected was analyzed using frequency, Cronbach’s alpha analysis, and Pearson correlation analysis using Statistical Package for the Social Sciences (SPSS) Version 22.0. From the 152 total number of respondents, 74 were males and 78 were females, 52 respondents have working experience of 1 to 2 years and 44 respondents have more than 2 years of working experience. 74 respondents are of more than 40 years old and 36 respondents are between 30 – 40 years old. All dimensions show more than 0.6 Cronbach’s Alpha range between 0.696 to 0.950 which may mean the consistency of the instruments are reliable and well-developed. The study also found that job autonomy, self-efficacy and mastery orientation do contribute to the job performance of the employees at work based on the correlation analysis with P-value less than 0.05. The results are parallel with the past study done by Saragih (2011), Iroegbu (2015), and Janssen (2004).